2009
DOI: 10.3844/ajidsp.2009.74.82
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clonal Clusters of Klebsiella pneumoniae Isolates from Chennai by Extended Spectrum Beta Lactamase Genotyping and Antibiotic Resistance Phenotyping Analysis

Abstract: Problem statement: An increased resistance to antibiotics has been reported in Klebsiella pneumoniae, an opportunistic gram negative pathogen belonging to Entrobacteraceae due to the evolution and spread of plasmid encoded extended spectrum beta lactamases and other genes conferring cross-resistance to other antibiotics. This is of concern due to the increasing cost of antibiotic treatment and the spread of multidrug resistance to more pathogenic microorganisms. This study was undertaken to analyze the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…In the present study, 72.7% of the strains carried the bla TEM gene, and the major subtype was TEM-1. These results are similar to those reported in India and Turkey, with a prevalence of 73% and 73.4%, respectively (10) (26) . Feizabadi et al conducted a similar study on K. pneumoniae strains in Hospitals of Tehran in 2007, and also found that TEM-1, SHV-12, and SHV-1 were the most prevalent subtypes (27) .…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, 72.7% of the strains carried the bla TEM gene, and the major subtype was TEM-1. These results are similar to those reported in India and Turkey, with a prevalence of 73% and 73.4%, respectively (10) (26) . Feizabadi et al conducted a similar study on K. pneumoniae strains in Hospitals of Tehran in 2007, and also found that TEM-1, SHV-12, and SHV-1 were the most prevalent subtypes (27) .…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, extended-spectrum beta-lactamaseproducing K.pneumoniae strains have become important pathogens in hospital-acquired infections, showing multi-resistance and causing more and more outbreaks in hospitals (Kamatchi et al, 2009). It is important to study the prevalence of K. pneumoniae in Milad Hospital in Tehran of Iran, as Iran is a fourseasoned country.…”
Section: Introductionmentioning
confidence: 99%
“…They differ from regular cephalosporinases by amino acid substitutions, insertions or deletions in four specific regionsthe Ω loop, the H-10 helix, the H-2 helix and the Cterminal extremity of the protein-all located in the vicinity of the active site (Rodriguez-Martinez et al, 2009). Moreover, an increased resistance to antibiotics has been reported in Pneumoniae as the widespread use of the third generation cephalosporins, β-lactam and broadspectrum antibiotics (Kamatchi et al, 2009;Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%